2014
DOI: 10.4137/bmi.s13059
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gene Signatures Used to Recognize Biological Characteristics of Gastric Cancer upon Gene Expression Data

Abstract: High-throughput gene expression microarrays can be examined by machine-learning algorithms to identify gene signatures that recognize the biological characteristics of specific human diseases, including cancer, with high sensitivity and specificity. A previous study compared 20 gastric cancer (GC) samples against 20 normal tissue (NT) samples and identified 1,519 differentially expressed genes (DEGs). In this study, Classification Information Index (CII), Information Gain Index (IGI), and RELIEF algorithms are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It has been reported that ATP4B, COL1A2 and HADHSC are the promising biomarkers [6][7][8]. ATP4B is diagnostically significant with apparent fold-changes in our previous study [9]. While exhibiting the potential power, there is no research report so far about the role of ATP4B expression in human cancers yet.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…It has been reported that ATP4B, COL1A2 and HADHSC are the promising biomarkers [6][7][8]. ATP4B is diagnostically significant with apparent fold-changes in our previous study [9]. While exhibiting the potential power, there is no research report so far about the role of ATP4B expression in human cancers yet.…”
mentioning
confidence: 63%
“…Gastric cancer is among the most common cancers gastrointestinal malignancies with few effective treatment strategies. Previous studies have reported that ATP4B is downexpressed in GC tissues related to poor prognosis in patients with GC [9,13,14]. However, there are few researches involving in the role of ATP4B in tumorigenesis and progression of human gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this, autoantibodies against ATP4B are regarded as serological diagnostic markers for patients with autoimmune atrophic gastritis, which are linked to an increased risk for gastric cancer [13]. Additionally, previous bioinformatics data have suggested that decreased ATP4B expressed in human GC tissue was substantially correlated with poor overall survival in patients with GC [14,15]. Therefore, further investigation into biological function of ATP4B in GC may improve understanding of the molecular mechanisms responsible for providing novel therapeutic targets of GC.…”
Section: Read Full License Introductionmentioning
confidence: 85%
“…The initiation and development of GC is a multi-stage, heterogeneous and multifactorial pathology process involving numerous genetic, epigenetic and environmental factors alterations [22]. Recently, studies have reported that the ATP4B gene is downregulated in GC, which plays a negative role in the progression of GC [6,15]. Restoring ATP4B expression in GC cells may heighten the inhibitory effects of chemotherapeutic drugs on GC cell growth [10].…”
Section: Discussionmentioning
confidence: 99%